Urgensi Pencabutan Perizinan Kegiatan Tambang Pasir Laut Sebagai Upaya Pelestarian Lingkungan Hidup Masyarakat Pesisir - Yusuf Kornelius (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
The re-legalization of sea sand mining activities is a controversial issue that significantly affects coastal communities. These mining activities can cause environmental damage and threaten the survival of coastal communities. This research aims to investigate the impact of re-legalized sea sand mining activities on coastal communities, with a focus on ecological, social and economic losses. The type of research used in this research is qualitative by analyzing findings from relevant research results. Research results show that sea sand mining activities have had a negative impact on ecosystems and communities around the coast. Sea sand mining causes marine habitat degradation, loss of fish resources, and economic uncertainty in coastal areas. Thus, absolute action is needed to protect coastal communities from the detrimental impacts caused by the sand mining industry